Evaluation of the Economic and Social Benefits from the Opening of Public Flower Gardens, the Psychological Impact on the Community - Mimoza Bytyqi-Maksutaj (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This scientific paper aims to evaluate the economic and social benefits of the opening of public flower gardens and to analyze the impact of these openings on the psychology of the population. Through a stable and analytical methodology, it is required to determine how the opening of public green spaces can contribute to improving the quality of life and well-being of citizens.The aim of this study is to identify and evaluate the concrete economic and social benefits of opening public flower gardens, including aspects of health, environment and social connections. Also, it is intended to understand how these spaces affect the psychology of the population and generally interact with the quality of life in the city. Methodology: The study will use a combination methodology, including statistical analysis of existing data, field surveys and case studies to collect and analyze various data. In order to evaluate the economic benefits, the causes related to the increase in economic activity will be used, while in order to evaluate the social benefits, the changes in the behavior and social relations of the citizens will be analyzed.